1974
DOI: 10.1177/030098587401100209
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Thymoma with Metastases in a Dog

Abstract: An 8-year-old male Wire-Haired Fox Terrier with respiratory distress and cough had a malignant thymoma that had metastasised to the lungs, spleen, liver, diaphragm, bronchial and mediastinal nodes, and pericardium by transcoelomic, vascular, and lymphatic routes. Myasthenia gravis, which occurs in some human patients with thymoma, was not evident.There are few reports of true thymomas in dogs [5]. TALERMAN and GWYNN [6] described one case and in a review of the literature found only five cases. WATSON and FARR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

1976
1976
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 6 publications
0
7
2
Order By: Relevance
“…Further sections of the entire mass were unavailable. Hassels corpuscles have been described in another case of malignant thymoma in a dog (Robinson, 1974), but they were not found in this case.…”
Section: H I S T O P a T H O L O G Ycontrasting
confidence: 59%
“…Further sections of the entire mass were unavailable. Hassels corpuscles have been described in another case of malignant thymoma in a dog (Robinson, 1974), but they were not found in this case.…”
Section: H I S T O P a T H O L O G Ycontrasting
confidence: 59%
“…Hassall's corpuscles usually present when the materials are fixed with formalin and stained with hematoxylin-eosin (H&E) (19). Some researchers have described structures resembling Hassall's corpuscles as an uncommon in thymoma (20) but in the present case these structures were seen. Paraneoplastic syndromes like myastenia gravis, exfoliative dermatitis, erythema multiforme, hypercalcemia, T-cell lymphocytosis, anemia and polymiositis are common in dogs and cats (21).…”
Section: Canine Thymomacontrasting
confidence: 56%
“…Metastatic lesions were not seen in the neoplasms reviewed in this study, although a canine thymoma is reported to have undergone metastasis and transcoelomic implantation [14]. Capsular invasion was a prominent feature in all three ovine thymomas in this study, and there were implantations of neoplastic cells upon the pericardium in the feline thymoma.…”
Section: Discussionmentioning
confidence: 57%